Keterlibatan Omk Dalam Memelihara Kelestarian Lingkungan Alam Sebagai Panggilan Spiritualitas Ensiklik “Laudato Si” - Pakpahan, Alek; Simarmata, Petrus (Pastoralia Jurnal Penelitian Dosen, 2025)
This research analyzes how Orang Muda Katolik (OMK) engages in environmental preservation as an expression of their faith, guided by the spirituality of Laudato Si'. Through a literature review, it examines OMK's environmental actions and their spiritual motivations, revealing their involvement in clean-up campaigns, reforestation, and environmental education as practical applications of Laudato Si' teachings. These teachings cultivate a sustainable and responsible mindset, integrating ecological action with their faith vocation. The study identifies challenges like limited resources and community support, alongside opportunities for Laudato Si' based formation programs and collaborations with various organizations. Ultimately, this research aims to increase OMK's environmental awareness and participation, contributing to environmental sustainability and quality of life, while providing academic insights into the practical implementation of Laudato Si' within the OMK community.